Technological change and skill obsolescence: the case of German apprenticeship training - Doris Blechinger; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
The paper analyses the applicability of vocational training and the earnings of apprentices using survey data from West Germany in 1979, 1985/86 and 1991/92. The applicability has decreased remarkably between 1979 and 1991/92. The objective of the analysis is a survey-data-based assessment of the German apprenticeship system in a time of rapid technological change. The data sets used are the three available cross-sections of Qualification and Career Surveys commissioned by the Federal Institute for Vocational Training and the Research Institute of the Federal Labour Office. For each cross-section we estimate an ordered probit model testing demand (including technological progress) and supply-side factors affecting the applicability of what workers have learned during apprenticeship. Furthermore, we estimate earnings functions with the same specification, testing whether firm-specific and socio-economic factors have the same relevance for applicability and earnings. The results indicate that on-the-job investment in human capital has become more important relative to vocational training. Measures for improving the German dual vocational training system are suggested.
Keywords: J21; J24; J62; 330; Duale Berufsausbildung; Humankapital; Erwerbsverlauf; Arbeitsmobilität; Technischer Fortschritt; Deutschland